Development of tablets containing probiotics: Effects of formulation and processing parameters on bacterial viability - Srikanjana Klayraung (2018)
The probiotic products available in the market nowadays are mostly in the form of liquid or semisolid formulations which show low cell viability after oral administration, mainly because the bacteria do not survive the harsh conditions in the stomach. The development of suitable dry dosage forms enable higher bacterial survival and consequently is the main aim of the present study. An anticipated advantage is that due to the low water-activity lyophilized bacterial cells will preserve their viability. Further, by a proper selection of a tablet forming matrix, it is foreseen that the entrapped bacteria are protected against the low pH in the stomach. In this study, the effects on bacterial survival in tablets were investigated concerning compression force, matrix forming excipients such as hydroxypropyl methylcellulose phthalate (HPMCP) or other swelling agents. The results showed that the proportion of matrix forming excipients in tablets and the compression force affected the properties of probiotic tablets in terms of tensile strength and disintegration as well as the survival of the bacteria. The tensile strength of the tablets increased with increase of HPMCP content. Tablets manufactured with high compression force showed a slow disintegration time and high bacterial cell viability (more than 80%). Incorporation of sodium alginate in the tablets resulted in higher cell survival in simulated GI fluid (>90%) and a suitable disintegration time (approximately 5 h). By a proper design of the formulation, tablets with a fast disintegration time and a high preservation of bacterial cell viability were developed. © 2008 Elsevier B.V. All rights reserved.